The Explications of Existential Despair in The Animals’ House of The Rising Sun - Reku, Angelina Merici Wua; Irawan, Muhammad Barra Sofyan Nur; Napitupulu, Johanes Claudio Perdana; Yuliastuti, Anicleta; Pasopati, Rommel Utungga (SALIENCE: English Language, Literature, and Education Journal, 2025)
This article explores into the concept of existential despair, as presented in The Animals' 1964 song House of the Rising Sun. The authors explore how the main character's personal journey grows important existentialist problems such as freedom, responsibility, regret, and the consequences of untrue existence by studying the song's lyrics. The authors of this article employ a qualitative method, which allows the reader to learn more about the object's background. By examining tone and symbolic imagery, the song changes into not only a warning but also a deep thought on what it means to experience life and awaken to the weight of one's own existence. In conclusion, this song is not only about melodic music, but it also contains song lyrics of existential despair as reflected in everyday points of human life.